Energy and communities in transition: Towards a new research agenda on agency and civil society in sustainability transitions - Gill Seyfang; Alex Haxeltine; Tom Hargreaves; Noel Longhurst (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2010)
The UK's energy transition (to a sustainable, low-carbon development path) may turn out to be highly dependant on the engendering and embedding of new types of social practice as well as on the widespread uptake of new low-carbon technologies. We argue that social change and social movements may be of vital importance in the energy transition, because the energy transition implies significant systems change and systems level innovations and not just individual-level behaviour change. Therefore market segmentation models that focus on behaviour change at the individual-level are missing the systemic implications of an energy transition. Behaviour change will likely occur in the context of changing values, lifestyles, and cultural norms modulated through social contexts, including social movements. This paper conceptualizes and theorizes the likely dynamics of social change and social movements in the context of an energy transition, explores a new empirical case study of the UKs transition movement and sets out elements of a research agenda designed to further explore these links. It does this by firstly presenting a case study, with new empirical evidence, of a civil society movement engaging in energy transitions, namely the Transition Towns movement. The Transition Towns movement provides an example of an emergent civil society movement with an agenda of instigating grassroots change directly rather than attempting to lobby or influence existing policy processes. The movement also presents its own formulations of what the end-point of an energy transition might be, emphasizing, for example, a localization of systems of production and consumption. Insights from the case study are then used to demonstrate how the current body of theory on 'sustainability transitions' can be extended to better include and address grassroots innovations, using insights from theories of social movements, and social practice theory. By extending current theory we conceptualize how social innovations link to macro-level systems change on the one hand and individual-level behaviour changes on the other hand. From this analysis we identify elements of an interdisciplinary research agenda for the empirical investigation of impacts of civil society movements for transition.
Keywords: 330; Energy transitions; Energieökonomik; Sozialer Wandel; Nachhaltigkeit; Gesellschaft; Energiepolitik; Theorie